Predição da máxima fase estável do lactato em adolescentes obesos ativos pelo limiar de concentração de proteínas totais salivares - Cunha, Heitor Santos (2012)
This study compared the total protein salivary threshold (TPST) and lactate threshold (LT) with maximal lactate steady state (MLSS) of active adolescents with obesity undergoing submaximal and maximal tests on a treadmill. The study included 16 obese, 6 boys and 10 women, (BMI = 34.1 ± 2.9 kg.m2) (age 15-19 years), all post-pubescent. Incremental test was performed (2 minutes of stage and 30 seconds of rest between stages) in air-conditioned environment (22-25 º C) until volitional exhaustion. The MLSS was assessed by performing submaximal running tests with a maximum duration of 30 minutes. The intensities of 55, 65, 75 and 85% of the velocity associated with VO2max (vVO2max) were randomly chosen. The velocities associated with the MLSS, TPST and LT were 6.7 ± 0.7, 6.5 ± 1.1 and 6.8 ± 1.1 km.h-1, respectively. There was no significant difference between the methods. Significant correlations were found between MLSS and LPTS (r = 0.56 and p <0.05), MLSS and LT (r = 0.66 and p <0.05), and LL/ LPTS (r = 0.60 and p <0, 05). In conclusion, active adolescents with obesity have TPST similar to MLSS and LT, demonstrating the applicability of this method for this population.